Development and testing of a nurse-led program to improve health privacy practices of nurses - Chin, Roren Marie M.
The growing complexities in healthcare have increased the risk to patients’ health data privacy violations and an overall unsafe delivery of basic health services. As coordinators of care, nurses spend the most time with patients managing their health data and are in a critical position to protect privacy or heighten the risk to privacy breaches. Despite the great need, there is a dearth of literature on effective initiatives to enhance the health privacy practices of nurses. Hence, developing interventions to improve health privacy practices of nurses and testing its efficacy in the real-world setting is a significant gap that needs to be filled to protect the healthcare consumers' rights to privacy.